Risk Management for 4-H Youth Development Work: Large Animals—Livestock - Chad Carr; Saundra Tenbroeck; Wendy DeVito; Chris Strong; Dale Pracht; Georgene Bender (EDIS)
Most people involved in youth livestock exhibition are familiar with the physical risks of handling and transporting livestock, but public spectators generally need more instruction and supervision to ensure their safety and health. The Risk Management for 4-H Youth Development Work series aims to provide UF/IFAS Extension county faculty, staff, volunteers, and youth with the knowledge they need to implement best practices in risk management strategies. This 8-page fact sheet covers risks in the following categories: injuries to people, injuries to animals, property damage, biosecurity (diseases transmitted to humans and between animals), and general precautions. Written by Chad Carr, Saundra TenBroeck, Wendy DeVito, Chris Strong, Dale Pracht, and Georgene Bender, and published by the UF Department of Animal Sciences, November 2015.